Managing Foreign R&D in China: Managers of international R&D and innovation in China relate the lessons they have learned—what works and what doesn't. Issue 3 (4th May 2018) - von Zedtwitz, Maximilian; Ikeda, Tadashi; Gong, Li; Carpenter, Richard; Hämäläinen, Seppo
OVERVIEW: China has become one of the most desired locations in which to do R&D. However, it has little innovation of its own, and intellectual property protection is weak. This raises questions: Is China R&D more hype than reality? Do cost advantages really outweigh the risk of losing technology to Chinese competitors? Lessons learned from managing R&D in China show that in order to avoid the typical pitfalls of managing R&D in a developing country, any China-based R&D must be part of an overall China strategy and must also be part of a global R&D effort.